The Method of High Order Fatigue Test of Thin Plate Composite Structure With Hard Coating - Li, Hui; Sun, Wei; Luo, Zhong; Wen, Bengchun (Journal of Applied Nonlinear Dynamics, 2026)
Foreign Object Debris (FOD) is debris or article alien, which may In order to solve the high order fatigue test problem of thin plate composite structure with hard coating, a new test method and its technological process is proposed based on the summarizing the experience of massive experiments. Besides, by considering technical difficulties of the high order fatigue test of the hard coating composite structure, several key techniques are described in details, such as how to measure dynamic strain without damaging the hard coating, how to predict excitation amplitude required by the high order fatigue test, and how to avoid the interference resulted from the strain softening of hard coating and to measure high order nature frequencies accurately. Finally, an experimental test is done to verify the practicability and reliability of this method.